2022
DOI: 10.1007/s10745-022-00336-2
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Rice Cultivation in Eastern Madagascar: Which Factors Matter to Smallholders, and Which Influence Food Security?

Abstract: In the eastern rainforests of Madagascar, rainfed swidden rice cultivation remains prevalent despite efforts to encourage uptake of irrigated systems to reduce deforestation. We used agricultural surveys with a stratified sample of 171 households to investigate constraints on and productivity of irrigated and rainfed rice perceived by farmers, and actual rice yields. Irrigated rice plots had higher median yields (1.72 t/ha compared to 0.62 t/ha), but farmers perceived the type of rice cultivation they practise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The length of the rainy season was from 70 (100) to 100 (140) days concerning rice (maize) crop needs. A previous paper by Dröge et al (2020) confirmed that pests and water were the factors limiting rice yields in eastern Madagascar. Furthermore, Barimalala et al (2021) pointed out that the North and East were subject to a deficit in total rainfall.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The length of the rainy season was from 70 (100) to 100 (140) days concerning rice (maize) crop needs. A previous paper by Dröge et al (2020) confirmed that pests and water were the factors limiting rice yields in eastern Madagascar. Furthermore, Barimalala et al (2021) pointed out that the North and East were subject to a deficit in total rainfall.…”
Section: Discussionmentioning
confidence: 89%
“…However, the rice fields, which have been divided for generations, diminish in size in the Highland of Madagascar (Andrianantoandro & Bélières, 2015). Moreover, smallholder farmers had constraints due to pests and weeds for rainfed rice and water management and infrastructure problems for irrigated rice in the eastern part of Madagascar (Dröge et al, 2020). On the other hand, global climate change effects would affect rice crop growth and production (Lanka, 2004; van Oort & Zwart, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results predicted that ruffed lemurs would avoid areas of the lowest ruggedness ( Figure 3 ). The reasoning for this may be twofold: low ruggedness areas of the eastern Ranomafana region are associated with increased anthropogenic presence and are preferentially used by humans for both irrigated and shifting agriculture (i.e., flooded rice paddies and slash-and-burn or tavy; [ 103 , 104 ]), whereas low ruggedness areas in the western region are associated with higher altitudes and shorter forest canopies [ 65 , 66 , 67 ]. In this way, similar to tigers, the ruffed lemurs in our study area are likely dispersing through the least rugged terrain that enables them to avoid anthropogenic landscapes while also remaining within their preferred tall-canopied habitats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One interesting avenue would be to examine the social and cultural factors that could enable households to transition away from shifting cultivation if they so wish, which has been investigated in the past from another angle, for example, through factors explaining the prevalence of this agricultural system (Laney & Turner, 2015). This could now be complemented with recent insights on biophysical factors that are locally perceived to constrain rice farming in eastern Madagascar (Dröge et al, 2022), or with perspectives highlighting the role that relational values may play in underpinning environmentally detrimental practices (Hoelle et al, 2021 [in this Special Issue]). Furthermore, in‐depth investigation of the influence of the recency bias we observed on views towards the PA, and how this plays out in the longer run, can provide insights on the psychological factors enabling or preventing acceptance of conservation interventions in forest frontier communities (St John et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One interesting avenue would be to examine the social and cultural factors that could enable households to transition away from shifting cultivation if they so wish, which has been investigated in the past from another angle, for example, through factors explaining the prevalence of this agricultural system (Laney & Turner, 2015). This could now be complemented with recent insights on biophysical factors that are locally perceived to constrain rice farming in eastern Madagascar (Dröge et al, 2022),…”
Section: Limitations and Outlookmentioning
confidence: 99%